2013
DOI: 10.1136/archdischild-2013-304778
|View full text |Cite
|
Sign up to set email alerts
|

Quality of reporting of studies evaluating time to diagnosis: a systematic review in paediatrics

Abstract: This study identified many weaknesses in the quality of reporting of studies of time to diagnosis in paediatrics, especially for items potentially related to risks of bias and variation. This finding underlines the need for the development of new (or the refinement of existing) guidelines for reporting this type of study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…Another has reported that time to diagnosis in 436 Ewing tumours in France was not associated with metastasis, surgical outcome or survival ( Brasme et al , 2014 ). One of our main findings, of the poor quality of reporting of time to diagnosis studies, replicates the findings of a recent paediatric systematic review ( Launay et al , 2013 ).…”
Section: Discussionsupporting
confidence: 83%
“…Another has reported that time to diagnosis in 436 Ewing tumours in France was not associated with metastasis, surgical outcome or survival ( Brasme et al , 2014 ). One of our main findings, of the poor quality of reporting of time to diagnosis studies, replicates the findings of a recent paediatric systematic review ( Launay et al , 2013 ).…”
Section: Discussionsupporting
confidence: 83%
“…Time to diagnosis (TTD) is the interval from first alert symptoms to the diagnosis of a disease in a patient [ 1 3 ]. Studies on TTD may aim at (1) measuring the length of TTD and its evolution over time, (2) identifying the determinants of long TTD (i.e., relationship between TTD and patient or healthcare system characteristics), and/or (3) evaluating relationships between long versus short TTD and patient outcomes [ 1 , 4 ]. The number of published studies on TTD is rapidly increasing [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…TTD is also of increasing concern among patient advocacy groups, and some, such as the International Confederation of Childhood Cancer Parent Organizations, have established a reduction in TTD as a priority [ 5 ]. There are strong and common beliefs that longer TTD is associated with worse health outcomes, as revealed by various systematic reviews of the literature [ 1 3 ]. Furthermore, in PubMed, the definition of the Medical Subject Heading “early diagnosis” includes the following statement: ‘ Generally, early diagnosis improves prognosis and treatment outcome ’ [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 As mentioned, all multivariable analyses of the associations between TtD and outcome were adjusted for trial arms. They emphasize that appropriate handling of covariables (such as treatments received and other prognostic factors) is a key issue in studies on the determinants and consequences of time to diagnosis (TtD).…”
mentioning
confidence: 99%